2011
DOI: 10.1038/bmt.2011.145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative and antioxidative parameters in pediatric hematopoietic SCT patients

Abstract: Conditioning regimens preceding hematopoietic SCT (HSCT) usually consist of high-dose chemotherapy. Chemotherapy and radiation therapy are associated with increased formation of free radicals and depletion of critical plasma and tissue antioxidants. Oxidative stress and antioxidant depletion have been described during the transplantation period in HSCT patients. In a limited number of studies, it was observed that the conditioning regimen resulted in oxidative stress and antioxidant depletion in HSCT patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…It seems that the effect of donor neutrophils is not greater than the effect of chemotherapy. We demonstrated that a conditioning regimen results in oxidative stress and depletion of antioxidants in pediatric HSCT patients in our previous study [15]. The results of this study indicate chronic oxidative stress in the plasma and erythrocytes of the patients, which increased gradually over a period of 28 days following chemotherapy and HSCT thereafter.…”
Section: Discussionmentioning
confidence: 63%
“…It seems that the effect of donor neutrophils is not greater than the effect of chemotherapy. We demonstrated that a conditioning regimen results in oxidative stress and depletion of antioxidants in pediatric HSCT patients in our previous study [15]. The results of this study indicate chronic oxidative stress in the plasma and erythrocytes of the patients, which increased gradually over a period of 28 days following chemotherapy and HSCT thereafter.…”
Section: Discussionmentioning
confidence: 63%
“…The role of oxidative stress (OS) is well known in the pathogenesis of acquired malnutrition [ 4 , 5 ]. Conditioning therapy given to HSCT recipients increases the production of reactive oxygen species and decreases the concentration of antioxidants and certain enzymes, vitamins E and C, and β-carotene [ 2 , 6 , 7 ]. This is probably responsible for the acute and delayed toxic effects that cytostatic drugs may have on tissues such as the gastrointestinal system, lungs, liver, or bladder [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, Trx1 reduced ROS accumulation in donor T cells and decreased Trx1 downstream molecules including NF-κB and T-bet, which restrained the ability of T cells to activate, expand, and migrate to the target organs in response to alloantigens in vivo. The contributions of preexisting disease conditions and the conditioning regimens increase cellular ROS, which correlates with elevated oxidative stress in all BMT recipients (8,9). Alloantigen-activated T cells exhibit higher cellular mitochondrial ROS generation and contain less antioxidant than their non-alloreactive counterparts (15).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress has been considered an unavoidable consequence of allo-HCT and may be an important factor in exacerbating GVHD (7). Owing to the contributions of preexisting disease conditions and the requirement for conditioning regimens that increase cellular reactive oxygen species (ROS), oxidative stress is elevated in all HCT recipients (8,9). Excess nitric oxide (NO) production was previously observed in both clinical GVHD (10,11) and experimental models (11,12).…”
Section: Introductionmentioning
confidence: 99%